The CDC (career development continuum) model as a basis for developing prototype career education modules for integration in the primary curriculum - Farolan, Sylvia J. 1936- (Education quarterly.)
This paper attempted to present Career Education modules integrating them into the primary grades curriculum of the 4th grade at International School using the Career Development Continuum model. The writer feels that the teaching-learning process being as complex as it is can be successfully accomplished with more optional materials to individualized instruction, the use of a variety of learning resources and a thorough and genuine cooperation among the teachers, counselors and administrators together with significant elements of the community.